Participation in sport and physical activity in adults with intellectual disabilities. Issue 12 (1st October 2020) - Borland, R. L.; Hu, N.; Tonge, B.; Einfeld, S.; Gray, K. M.
Abstract: Background: People with intellectual disability face a number of barriers to participation in physical activity. This paper aimed to determine rates of sport and physical activity participation in an Australian sample of adults with intellectual disability, compared with rates of participation in the general Australian population. A secondary aim was to investigate factors that may contribute to participation of adults with intellectual disability. Method: Participants were part of the Australian Child to Adult Development (ACAD) study, consisting of a community sample with intellectual disability ( n  = 305), groups of adults with autism ( n  = 94), Down syndrome ( n  = 64), fragile X syndrome ( n  = 52), Williams syndrome ( n  = 45), and Prader–Willi syndrome ( n  = 30). Participation in sport/physical activity was reported over the past 3 months. Rates of participation were reported for adults with intellectual disability and compared with rates in a general Australian population sample. The relationship between participation in physical activity and age, degree of intellectual disability, physical mobility, living situation, socio‐economic disadvantage, and behaviour and emotional problems were also conducted. Results: Participants in the ACAD community sample with intellectual disability participated in sport/physical activity at lower rates than the general Australian population (42% compared with 71%). Having no physical mobility impairment was significantly associated with higher rates of participation. Those with Down syndrome participated in sport/physical activity at higher rates than the community sample with intellectual disability, while no difference in sport/physical activity participation was observed in the groups with autism or other syndromes. Conclusion: Australian adults with intellectual disability participate in sport and physical activity at lower rates than the general population. Having a physical mobility impairment was associated with lower rates of participation. However, people living in supported accommodation were more likely to participate than those in other living situations. Having Down syndrome was associated with a higher participation rate than the community sample.